Lowering Blood Pressure of Hypertension through Benson Relaxation - Dewiyuliana Dewiyuliana (STIKes Patria Husada Blitar, 2023)
Hypertension is a chronic non-communicable disease, the cases of which are increasing every years. Hypertension is caused by heredity, age, food and unhealthy lifestyle. The consequences of hypertension include heart disease, stroke, myocardial infarction, atherosclerosis, kidney failure and other diseases. One of the effective and easy non-pharmacological treatments for lowering blood pressure is using Benson relaxation. Benson's relaxation is a concentration of relaxation by harmonizing blood pressure so that it reduces the work of the sympathetic and initial sympathetic nerves to affect heart rate, pulse, respiration and activities that use the workload of the heart. This study aimed to analyze the effect of benson relaxation in reducing blood pressure in hypertensive patients. This study was a pre-experimental research with a pretest and posttest design approach. The population in this study was hypertensive patients with a sample of 18 respondents selected by purposive sampling with the criteria of being willing to become respondents and participating in Benson relaxation activities for 2 weeks. The hypothesis testing used the T test (Paired sample Test). The results of the pre post systole study obtained p = 0.000 and pre post diastole p = 0.007 indicating that Benson relaxation is done regularly and is effective in reducing blood pressure in people with hypertension. It is hoped that people and families with hypertension can apply Benson in reducing and controlling blood pressure